Improving Worship Discipline and Focus Through Prayer Reminder Apps - Paradisa, Walada; Nabhila, Dhiana Ratu; Alhafidza, Naylazyani Siti; Surahman, Cucu (PT. Student Rihlah Indonesia, 2025)
This study investigates the impact of prayer reminder applications on worship discipline and spiritual focus (khusyuk) among Muslim university students in Bandung, Indonesia. The research aims to assess the effectiveness of such apps in enhancing prayer punctuality and spiritual engagement. Using a quantitative explanatory method, data were gathered from 33 users of apps like Muslim Pro and Al-Quran Indonesia. Results show significant improvement in prayer timeliness (mean: 4.1/5) though the improvement in khusyu’ was more modest (mean: 3.0/5). Key obstacles include poor internet (35%), app errors (30%), and inconsistent alerts (25%). The findings suggest that while digital nudges improve external discipline, they are less effective in fostering inner devotion. This study’s novelty lies in its integration of behavioral nudging with Islamic educational values. It recommends features like offline access and reflective prompts to support both compliance and spiritual depth. These insights offer implications for Islamic app developers and educators aiming to enhance faith-tech experiences.